Public Investment Boosted Private Investment in Brazil between 1982 and 2013. Issue 3 (3rd July 2019) - de Borja Reis, Cristina Fróes; de Araújo, Eliane Cristina; Gonzales, Erica Oliveira
Abstract: The aim of this study is to investigate whether the so-called crowding in effects of complementarity or the crowding out effects of substitution occurred between public investment and private investment in Brazil from 1982 to 2013. This will be carried out through a theoretical debate on the investment general dynamics and an econometric analysis of vector error correction (VEC) model for the Brazilian case. The trajectory of the Brazilian economy and the empirical results show the presence of crowding in between public and private investments in the period, in accordance with the Post-Keynesian approaches. The crowding in is justified by the effects on demand via the Keynesian multiplier and via the expansion of the domestic market (particularly provided by infrastructure) and by the effects on the supply of private capital through the reduction of production costs, the increase in productivity, and through structural changes facilitated by public policy. Complementarity with regard to both the investments of the public administration and of federal government-owned/controlled enterprises is confirmed. Furthermore, a significant causal relationship is observed between public investment and the output of industrial manufacturing, which, from the structuralist perspective, is a sector that is considered a driving force of the economy. The special contributions of this paper are its time series for public investment and the variety of models that show crowding in between public and private investment.